2020
DOI: 10.1084/jem.20200474
|View full text |Cite
|
Sign up to set email alerts
|

Multi-omic comparison of Alzheimer’s variants in human ESC–derived microglia reveals convergence at APOE

Abstract: Variations in many genes linked to sporadic Alzheimer’s disease (AD) show abundant expression in microglia, but relationships among these genes remain largely elusive. Here, we establish isogenic human ESC–derived microglia-like cell lines (hMGLs) harboring AD variants in CD33, INPP5D, SORL1, and TREM2 loci and curate a comprehensive atlas comprising ATAC-seq, ChIP-seq, RNA-seq, and proteomics datasets. AD-like expression signatures are observed in AD mutant SORL1 and TREM2 hMGLs, while integrative multi-omic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 90 publications
8
39
0
Order By: Relevance
“…Whether the changes in exosomal protein content are due to changes in protein packaging or underlying differences in the iPS-Mg themselves was analysed in a subset of identified proteins in this study. In line with another study [60], R47H het iPS-Mg displayed an increased expression of DAM-related genes (overall Fig 2 C is confusing to the rest of the paper) which translated to basal R47H het exosomes containing higher levels of DAM-related proteins, in comparison with basal Cv exosomes ( Fig 2 ). Whilst other studies have found an increase in microglia expressing DAM genes in animals treated with LPS [39,61] this was not replicated in this study.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Whether the changes in exosomal protein content are due to changes in protein packaging or underlying differences in the iPS-Mg themselves was analysed in a subset of identified proteins in this study. In line with another study [60], R47H het iPS-Mg displayed an increased expression of DAM-related genes (overall Fig 2 C is confusing to the rest of the paper) which translated to basal R47H het exosomes containing higher levels of DAM-related proteins, in comparison with basal Cv exosomes ( Fig 2 ). Whilst other studies have found an increase in microglia expressing DAM genes in animals treated with LPS [39,61] this was not replicated in this study.…”
Section: Discussionsupporting
confidence: 85%
“…Whether the changes in exosomal protein content are due to changes in protein packaging or underlying differences in the iPS-Mg themselves was analysed in a subset of identified proteins in this study. In line with another study [60] [39,61] this was not replicated in this study. This could be due to differences between murine and human microglia, or the time course of the experiments.…”
Section: Influence Of Trem2 On Exosomes From Ips-mgsupporting
confidence: 76%
“…Our cerebrovascular tissue showed moderate expression of glial markers, therefore some of the APOE specific effects we observed could be driving in part by changes in these cell types, which are the main producers of APOE in the brain [33]. APOE4 genotype has been demonstrated to influence the phenotypic change of astrocytes into the A1 disease phenotype, and also convert microglia into neurotoxic entities that produce proinflammatory cytokines [105,[108][109][110][111][112]. In AD, glial cell inflammation could therefore serve as critical determinants driving the immune response that contributes to the damage of cerebrovessels.…”
Section: Apoe Specific Effects On Cerebrovascular Proteome In Admentioning
confidence: 99%
“…Our findings add to a growing literature demonstrating shifts in microglial gene expression across various states and diseases, including transcriptional signatures associated with specific DAM subpopulations ( Rangaraju et al., 2018 ), with different stages of neurodegeneration ( Mathys et al., 2017 ), and with aging in both human ( Olah et al., 2018 ) and mouse ( Hammond et al., 2019 ) microglia. Recent reports have also demonstrated a role for APOE in the context of microglial gene expression ( Liu et al., 2020 ; Sala Frigerio et al., 2019 ). For instance, TREM2-dependent APOE signaling is necessary for expression of the DAM phenotype, and blocking this pathway restores homeostatic microglia while reducing neuron loss ( Krasemann et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%